2008
DOI: 10.1590/s1519-69842008000300024
|View full text |Cite
|
Sign up to set email alerts
|

Bipedal locomotion in Tropidurus torquatus (Wied, 1820) and Liolaemus lutzae Mertens, 1938

Abstract: Bipedalism has evolved on numerous occasions in phylogenetically diverse lizard families. In this paper we describe, for the first time, bipedal locomotion on South American lizards, the sand-dweller Liolaemus lutzae and the generalist Tropidurus torquatus. The lizards were videotaped running on a racetrack and the sequences were analyzed frame by frame. The body posture, as a whole, diverged a lot during bipedal locomotion between the two species, even though there was no difference regarding their sprint per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The bipedal gait of A. sexlineata does not match the described gait for any one species but it most closely resembles that observed in Aspidoscelis tigris, despite A. sexlineata's smaller size (Urban, 1965;Irschick and Jayne, 1999a). Overall hindlimb movements were characterized by a vertical orientation of the femur and digitigrade posture throughout stance, which is consistent with previous descriptions of bipedal locomotion in Callisaurus draconoides (Irschick and Jayne, 1999a) and Liolaemus lutzae (Rocha-Barbosa et al, 2008). Trunk angle was highly variable during bipedal running, as was position of the forelimb.…”
Section: Comparisons With Other Taxasupporting
confidence: 87%
See 1 more Smart Citation
“…The bipedal gait of A. sexlineata does not match the described gait for any one species but it most closely resembles that observed in Aspidoscelis tigris, despite A. sexlineata's smaller size (Urban, 1965;Irschick and Jayne, 1999a). Overall hindlimb movements were characterized by a vertical orientation of the femur and digitigrade posture throughout stance, which is consistent with previous descriptions of bipedal locomotion in Callisaurus draconoides (Irschick and Jayne, 1999a) and Liolaemus lutzae (Rocha-Barbosa et al, 2008). Trunk angle was highly variable during bipedal running, as was position of the forelimb.…”
Section: Comparisons With Other Taxasupporting
confidence: 87%
“…Many groups, including cockroaches, lizards, small rodents and primates, can run using differing numbers of limb pairs, but only cockroaches and lizards must start running using all limb pairs before transitioning to a bipedal gait in the same locomotor bout (Snyder, 1952;Djawdan and Garland, 1988;Full and Tu, 1991;Thorpe et al, 2007). Despite its widespread occurrence in lizards, the mechanisms and advantages of bipedal locomotion are poorly understood (Snyder, 1949;Snyder, 1952;Snyder, 1962;Urban, 1965;Irschick and Jayne, 1999a;Irschick and Jayne, 1999b;Aerts et al, 2003;Clemente et al, 2008;Rocha-Barbosa et al, 2008). Early studies have suggested that bipedal running in lizards is inherently faster than quadrupedal locomotion, similar to bipedal locomotion in cockroaches (Snyder, 1962;Full and Tu, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Many lizard and rodent species have lower escape speeds in dense vegetation compared with open areas (Vasquez et al, 2002;Schooley et al, 1996;Goodman, 2009;Vanhooydonck and Van Damme, 2003). Species utilizing bipedal running may be able to exploit habitat types with uneven substrata because of the increases in visual perception and/or by reaching their maximum speed more quickly (Rieder et al, 2010;Djawdan and Garland, 1988;Rocha-Barbosa et al, 2008;Kohlsdorf and Biewener, 2006). Because two obstacles create the same negative performance effect on stride characteristics and velocity, bipedalism is likely only beneficial when negotiating a single obstacle (Fig.…”
Section: Performance and Behavior With Multiple Obstaclesmentioning
confidence: 99%
“…Some agamid species, such as the crested dragon Ctenophorus cristatus, are known for their long bipedal excursions over uneven terrain [6]. The south American iguanid lizards Liolaemus lutzae and Tropidurus torquatus perform sustained bipedal running on beach or dune sand [7]. Basilisk lizards (Basiliscus sp.)…”
Section: Introductionmentioning
confidence: 99%